Shaping transdisciplinary, challenge-based education using knowledge creating teams from five European universities: A realist evaluation - O'Sullivan, Gemma (Trinity College Dublin. School of Education. Discipline of Education, 2023)
There are increasing calls both within universities (Gibbons, Limoges, Nowotny, Schwartzman, Scott & Trow, 1994; Sterling, 2004; Stauffacher, Walter, Lang, Wiek & Scholz, 2006; Kueffer, Underwood, Hirsch Hadorn, Holderegger, Lehning, Pohl, ? Wuelser & Edwards, 2012; Cincera, Biberhofer, Binka, Boman, Mindt & Rieckmann, 2018; Fam, Neuhauser & Gibbs, 2018) and external to universities (European Commission, 2017, 2019, 2020) for the academy to innovate to address grand societal challenges. Transdisciplinarity (TD) has emerged both in policy and academia as a framework to purportedly drive this innovation through engaging research with societal needs; breaking down disciplinary `silos? within the university and developing competencies or transversal skills to make education impactful (Barth, Adom?ent, Fischer, Richter & Rieckmann, 2014; Gibbs, 2017). However, despite European policy calls for TD (Horizon Europe Missions ? ongoing; European Universities Initiative, 2021) evidence on how to implement TD and its impact educationally is lacking. This diminishes its potential for sectoral change. Added to this, there are multiple definitions, approaches and foci within TD (Fam & O?Rourke, 2021; Klein, 2009). While there is a growing body of research informing the operation of TD research (Pohl & Hirsch Hadorn, 2007; Klein, 2014; von Wehrden, Guimar?es, Bina, Varanda, Lang, John? Lawrence, 2019; Baptista & Rojas-Castro, 2020), to date research on TD education comprises case studies by academics outside the discipline of education (Klein, 2018; Fam, Neuhauser & Gibbs, 2018). Further evidence is needed on how TD curricula are created, how disciplinary knowledge from multiple disciplines is integrated and what pedagogical approaches support and comprise TD education. This thesis sought to contribute to building a body of evidence to support the development of TD education within universities by opening the black box on how TD curricula are formed and focusing on how Knowledge Creating Teams (KCTs), multi-disciplinary groups of academics, created a TD master?s in global challenges for sustainability. The key research question was: How can TD education be successfully created in a university? To `open the black box? of TD curriculum design, I adopted a critical realist stance and applied realist evaluation (RE) as an analytical framework to an EC-funded ?experiment? wherein a five-university alliance piloted the creation of a TD university through the use of trans-institutional, TD KCTs to design a challenge-driven, TD master?s programme. I generated data through two phases of ten semi-structured interviews with KCT members, and, through my role as research associate within the Alliance i.e. a research diary, memos, catalogue of emails, video recordings and Alliance documents. The evaluation tested a program theory and I used a case study to draw a boundary around the components of that program theory as situated within the Alliance. Through the framework of RE, the findings demonstrate a set of principles that can inform the design of trans-institutional and institutional TD programmes. These demonstrate that KCTs are an effective means to innovate systems and leverage institutional strengths to drive responsive TD educational and research initiatives. However, the findings also confirm existing literature on TD education and research which articulates the need for further research to test and strengthen integration methodologies to create TD curricula. The thesis concludes with a series of system recommendations to inform higher education policy and practice pertaining to TD and challenge-driven education (CDE). ?
APPROVED
Keywords: challenge-based learning; higher education; critical realism; realist evaluation; transdisciplinarity; European university; curriculum design